CERA‐20C: A Coupled Reanalysis of the Twentieth Century. (21st May 2018) - Laloyaux, Patrick; de Boisseson, Eric; Balmaseda, Magdalena; Bidlot, Jean‐Raymond; Broennimann, Stefan; Buizza, Roberto; Dalhgren, Per; Dee, Dick; Haimberger, Leopold; Hersbach, Hans; Kosaka, Yuki; Martin, Matthew; et al.
Abstract: CERA‐20C is a coupled reanalysis of the twentieth century which aims to reconstruct the past weather and climate of the Earth system including the atmosphere, ocean, land, ocean waves, and sea ice. This reanalysis is based on the CERA coupled atmosphere‐ocean assimilation system developed at ECMWF. CERA‐20C provides a 10 member ensemble of reanalyses to account for errors in the observational record as well as model error. It benefited from the prior experience of the retrospective atmospheric analysis ERA‐20C. The dynamical model and the data assimilation systems initially developed for NWP had been modified to take into account the evolution of the radiative forcing and the observing system. To limit the impact of changes in the observing system throughout the century, only conventional surface observations have been used in the atmosphere. CERA‐20C improves the specification of the background and the observation errors, two key elements to ensure a consistent weighting of the uncertainties across geophysical variables, space, and time. The quality of CERA‐20C has been evaluated against other centennial reanalyses and independent observations. Although CERA‐20C inherits some limitations of ERA‐20C to represent correctly the tropical cyclones in the first part of the century, it shows significant improvements in the troposphere, compared to ERA‐20C and 20CRv2c (the twentieth century reanalysis produced by NOAA/CIRES). A preliminary study of the climate variability in CERA‐20C has been carried out. CERA‐20C improves on the representation of atmosphere‐ocean heat fluxes and mean sea level pressure compared to previous uncoupled ocean and atmospheric historical reanalyses performed at ECMWF. Key Points: CERA‐20C reconstructs the past climate of the atmosphere, ocean, land, waves, and sea ice CERA‐20C provides a 10 member ensemble of reanalyses to account for errors CERA‐20C shows significant improvements in the troposphere, compared to ERA‐20C and 20CRv2c